2022
DOI: 10.3389/ijph.2022.1605188
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life: Updated Psychometric Properties and New Norm Values in a Representative German Sample Focusing Socioeconomics and Mental Health

Abstract: Objectives: Quality of life (QOL) is increasingly used as indicator in health research. The aim of this paper was an updated psychometric validation and a new standardization of the German version of the EUROHIS-QOL using a sample of the German general population assessed in 2021. The study focused on socio-economic characteristics and on anxiety and depressiveness as major indicators of mental health.Methods: With 8 items, the EUROHIS-QOL is an economical instrument for self-assessment.Results: Statistical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
3
6
1
Order By: Relevance
“…In 2020 and 2021, men and women differed significantly in their QoL with women reporting a lower sum score. This is in line with publications concerning QoL in men and women in the German population [ 13 15 ]. Our results also show, as one of the first longitudinal analysis during the pandemic, that quality of life as measured by the EUROHIS-QOL was significantly lower at the second measurement time point during the pandemic for both men and women, indicating that the ongoing pandemic and its measures were increasingly stressful for the general German population.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In 2020 and 2021, men and women differed significantly in their QoL with women reporting a lower sum score. This is in line with publications concerning QoL in men and women in the German population [ 13 15 ]. Our results also show, as one of the first longitudinal analysis during the pandemic, that quality of life as measured by the EUROHIS-QOL was significantly lower at the second measurement time point during the pandemic for both men and women, indicating that the ongoing pandemic and its measures were increasingly stressful for the general German population.…”
Section: Discussionsupporting
confidence: 92%
“…This is partly in line with previous studies which identified migration background as a risk factor for QoL [ 15 , 23 25 ]. Moreover, higher SES was previously associated with higher QoL [ 15 , 26 ]. Thus, as hypothesized especially socially disadvantaged individuals showed lower QoL.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As no other studies examining QoL using a similar scale for the general population in Jordan are known, we found two recent studies that used the same EUROHIS-QOL scale to measure QoL among the adult population in Germany and Saudi Arabia during the COVID-19 pandemic. These studies reported higher scores of 3.95 and 3.91, respectively, compared to the healthcare workers in Jordan who were the focus of the current study [41,42].…”
Section: Discussionmentioning
confidence: 78%